2003
DOI: 10.1046/j.1600-0420.2003.0213.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pterygium in an adult Jordanian population

Abstract: ABSTRACT.Purpose: To evaluate the risk factors for the development of pterygium in a Middle Eastern country (Jordan) and to compare our findings with those from other countries. Methods: This study was conducted in Irbid District, in northern Jordan, a region located 31 degrees north of the equator, with a stable, subtropical climate. In this case control study, 96 adult subjects presenting with pterygium were interviewed and compared to 192 control subjects who were group-matched for age and sex. A standard q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 29 publications
3
50
0
1
Order By: Relevance
“…4,6,12,16 There are also reports indicating higher prevalence rates among women, 5,13 and yet some studies found no correlation between pterygium and gender (Table 4). 11,15,17,18 On the basis of the results of this study, the prevalence of pterygium significantly increases with age in both genders. These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age.…”
Section: Discussionmentioning
confidence: 66%
“…4,6,12,16 There are also reports indicating higher prevalence rates among women, 5,13 and yet some studies found no correlation between pterygium and gender (Table 4). 11,15,17,18 On the basis of the results of this study, the prevalence of pterygium significantly increases with age in both genders. These results are similar to those by other studies, and most of them confirm that there is a correlation between pterygium and age.…”
Section: Discussionmentioning
confidence: 66%
“…The risk factors for pterygium includes ultraviolet radiation exposure, dry climatic conditions and genetics. 1,6,7,9 Indication for the treatment of pterygium includes;…”
Section: 10mentioning
confidence: 99%
“…16 Pterjium prevelansının %1,1-%23,4 olduğunu belirten çalışmalar mevcuttur. 14,[17][18][19] Pterjium prevalansı Amerika Birleşik Devletleri'nde %2-7, Avustralya'da %1,1, Pekin'de %3, Tahran'da %1,3, Myanmar'da tek gözde %19,6, her iki gözde %8, Endonezya'da tek gözde %10, her iki gözde %4,1 saptanmıştır. [20][21][22][23][24][25] Bizim çalışmamızda bu oran %7,8 idi.…”
Section: Discussionunclassified